Paraventricular Hypothalamic Mechanisms of Chronic Stress Adaptation - Herman, James P.; Tasker, Jeffrey G. (Frontiers in Endocrinology, 2016)
The hypothalamic paraventricular nucleus (PVN) is the primary driver of hypothalamo-pituitary-adrenocortical responses. At least part of the role of the PVN is managing the demands of chronic stress exposure. With repeated exposure to stress, hypophysiotrophic corticotropin-releasing hormone (CRH) neurons of the PVN display a remarkable cellular, synaptic and connectional plasticity that serves to maximize the ability of the HPA axis to maintain response vigor and flexibility. At the cellular level, chronic stress enhances production of CRH and its co-secretagogue arginine vasopressin (AVP), and rearranges neurotransmitter receptor expression so as to maximize cellular excitatbility. There is also evidence to suggest that efficacy of local glucocorticoid feedback is reduced following chronic stress. At the level of the synapse, chronic stress enhances cellular excitability and reduces inhibitory tone. Finally, chronic stress causes a structural enhancement of excitatory innervation, increasing the density of glutamate and noradrenergic/adrenergic terminals on CRH neuronal cell somata and dendrites. Together, these neuroplastic changes favor the ability of the HPA axis to retain responsiveness even under conditions of considerable adversity. Thus, chronic stress appears able to drive PVN neurons via a number of convergent mechanisms, processes that may play a major role in HPA axis dysfunction seen in variety of stress-linked disease states.